Evaluation of conservative approach in the management of ureteroenteric strictures following radical cystectomy with Bricker ileal conduit: a single-center experience. (1st November 2016) - Baten, Evert; Akand, Murat; Floyd, Michael S.; Van Cleynenbreugel, Ben; Albersen, Maarten; Everaerts, Wouter; Van Poppel, Hendrik; Van Der Aa, Frank; Joniau, Steven
Abstract: Objective: The aim of this study was to evaluate the risk factors and treatment options for ureteroenteric strictures (UES) following radical cystectomy (RC) and ileal conduit (IC) formation, and specifically to comment on the conservative management of UES in asymptomatic patients. Materials and methods: The datasheets were reviewed of 304 consecutive patients who were treated with an RC and IC between January 2001 and May 2011 in a Belgian tertiary center and who followed a strict follow-up protocol. Long-term treatment outcomes were retrospectively analyzed. Results: Twenty-two patients (7.2%) were diagnosed with UES (affecting 27 ureters in total), when a new-onset hydroureteronephrosis or increase of the pre-existing hydroureteronephrosis was detected by ultrasound or computed tomography. A retrograde loopogram was then performed to confirm the UES. The mean follow-up time was 33 months. A decline in renal function, the presence of flank pain and urinary tract infections were indications for interventional treatment. Six patients underwent double-J stent placement, two patients received percutaneous nephrostomies as a definitive treatment and two patients underwent ureterointestinal reimplantation. Asymptomatic patients with a UES and a favorable renal function were conservatively managed. They remained asymptomatic during follow-up and required no active treatment. Conclusions: No clinical variable was independently associated with an increased risk of UES. These long-term data suggest that a selected patient population of asymptomatic patients with good renal function at the time of UES diagnosis can be safely managed conservatively.